"Rights without Access": The Political Context of Inequality in Health Care Coverage in the U.S. States. (June 2015) - Zhu, Ling; Clark, Jennifer H.
Abstract: The question of how the American political process shapes inequality remains unsettled. While recent studies break ground by linking inequality to political institutions, much of this work focuses on national-level income inequality. The literature is lacking in its examination of inequality in other issue areas at the subnational level. This research explores how partisanship in government affects subnational-level inequality in health care coverage in the context of racial diversity. Using a new Gini-coefficient measure of inequality in health insurance coverage, we find a negative relationship between the seat share of Democratic representatives and inequality in health care coverage but only in states with racially diverse populations. Moreover, Democratic-controlled state legislatures mitigate the negative impact of racial diversity on inequality in health care coverage. These results highlight the importance of examining the partisan foundation of health care inequality in the context of racial diversity.